2017
DOI: 10.1161/strokeaha.117.016579
|View full text |Cite
|
Sign up to set email alerts
|

XBP1 (X-Box–Binding Protein-1)–Dependent O-GlcNAcylation Is Neuroprotective in Ischemic Stroke in Young Mice and Its Impairment in Aged Mice Is Rescued by Thiamet-G

Abstract: Background and Purpose Impaired protein homeostasis induced by endoplasmic reticulum (ER) dysfunction is a key feature of a variety of age-related brain diseases including stroke. To restore ER function impaired by stress, the unfolded protein response (UPR) is activated. A key UPR pro-survival pathway is controlled by the ER stress sensor inositol-requiring enzyme-1 (IRE1), downstream X-box binding protein-1 (XBP1), and O-linked b-N-acetylglucosamine (O-GlcNAc) modification of proteins (O-GlcNAcylation). Stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 35 publications
4
61
0
Order By: Relevance
“…These findings suggest that aging is associated with a decline in the capacity of cells to activate these posttranslational modifications, particularly SUMOylation and O‐GlcNAcylation. Rapid activation of both modifications has been reported in various postischemic organs 6, 8, 27, 28, 29, 30. Notably, in the present study, these were the only posttranslational modifications that showed impaired activation in both brain and kidney of aged mice.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…These findings suggest that aging is associated with a decline in the capacity of cells to activate these posttranslational modifications, particularly SUMOylation and O‐GlcNAcylation. Rapid activation of both modifications has been reported in various postischemic organs 6, 8, 27, 28, 29, 30. Notably, in the present study, these were the only posttranslational modifications that showed impaired activation in both brain and kidney of aged mice.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, it is reasonable to propose that at advanced age, cells are more sensitive to a severe form of stress that impairs proteostasis. Indeed, such findings have been recently reported after myocardial ischemia and stroke 8, 18. For CA, however, the role of aging‐related decline in the capacity of cells to restore proteostasis impaired by I/R stress has not yet been considered a potential contributor to worse outcome in elderly individuals.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations